Augmented Expansion of Treg Cells From Healthy and Autoimmune Subjects via Adult Progenitor Cell Co-Culture - Reading, James L.; Roobrouck, Valerie D.; Hull, Caroline M.; Becker, Pablo Daniel; Beyens, Jelle; Valentin-Torres, Alice; Boardman, Dominic; Lamperti, Estefania Nova; Stubblefield, Samantha; Lombardi, Giovanna; Deans, Robert; Ting, Anthony E.; et al. (Frontiers in immunology, 2021)
Recent clinical experience has demonstrated that adoptive regulatory T (Treg) cell therapy is a safe and feasible strategy to suppress immunopathology via induction of host tolerance to allo- and autoantigens. However, clinical trials continue to be compromised due to an inability to manufacture a sufficient Treg cell dose. Multipotent adult progenitor cells (MAPC Ⓡ ) promote Treg cell differentiation in vitro , suggesting they may be repurposed to enhance ex vivo expansion of Tregs for adoptive cellular therapy. Here, we use a Good Manufacturing Practice (GMP) compatible Treg expansion platform to demonstrate that MAPC cell-co-cultured Tregs (MulTreg) exhibit a log-fold increase in yield across two independent cohorts, reducing time to target dose by an average of 30%. Enhanced expansion is coupled to a distinct Treg cell-intrinsic transcriptional program characterized by elevated expression of replication-related genes ( CDK1, PLK1, CDC20 ), downregulation of progenitor and lymph node-homing molecules ( LEF1 CCR7, SELL ) and induction of intestinal and inflammatory tissue migratory markers ( ITGA4, CXCR1 ) consistent with expression of a gut homing (CCR7lo β 7 hi) phenotype. Importantly, we find that MulTreg are more readily expanded from patients with autoimmune disease compared to matched Treg lines, suggesting clinical utility in gut and/or T helper type1 (Th1)-driven pathology associated with autoimmunity or transplantation. Relative to expanded Tregs, MulTreg retain equivalent and robust purity, FoxP3 Treg-Specific Demethylated Region (TSDR) demethylation, nominal effector cytokine production and potent suppression of Th1-driven antigen specific and polyclonal responses in vitro and xeno Graft vs Host Disease (xGvHD) in vivo . These data support the use of MAPC cell co-culture in adoptive Treg therapy platforms as a means to rescue expansion failure and reduce the time required to manufacture a stable, potently suppressive product.